Development and Characterization of Al6061-Zirconium Dioxide Reinforced Particulate Composites - S, Udayashankar; S.Ramamurthy, V (International Journal of Engineering and Technology, 2018)
Particulate reinforced Aluminium based metal matrix composites are widely used in aerospace, defense, marine and space applications because their excellent properties such as high strength, high stiffness, high corrosion resistance, high fatigue resistance, high wear resistance etc., In the present work Aluminum Alloy Al6061-Zirconium dioxide composites were developed by stir casting technique by varying the percentage of Zirconium dioxide in steps of 3% up to 12%.The samples were prepared as per ASTM standards for microstructure study, tensile strength and hardness properties. The microstructure studies carried using optical microscope revealed the presence of Zirconium dioxide particulates in the Aluminium matrix. Also it revealed the uniform distribution of Zirconium dioxide in the Aluminium matrix and no voids and porosity were present in the matrix. The tensile strength and hardness properties were more than the base metal aluminium alloy. The tensile strength and hardness properties were increased with the increase in percentage of Zirconium dioxide up to 9% and decreased there afterwards. The optimum value for hardness and tensile strength of the composite was obtained at 9% of Zirconium dioxide.Â Â Â